Perforator mapping reduces the operative time of DIEP flap breast reconstruction: A systematic review and meta-analysis of preoperative ultrasound, computed tomography and magnetic resonance angiography. Issue 4 (April 2018) - Wade, Ryckie G.; Watford, James; Wormald, Justin C.R.; Bramhall, Russell J.; Figus, Andrea
Summary: Background: Prior to DIEP flap breast reconstruction, mapping the perforators of the lower abdominal wall using ultrasound, computed tomography angiography (CTA) or magnetic resonance angiography (MRA) reduces the risk of flap failure. This review aimed to investigate the additional potential benefit of a reduction in operating time. Methods: We systematically searched the literature for studies concerning adult women undergoing DIEP flap breast reconstruction, which directly compared the operating times and adverse outcomes for those with and without preoperative perforator mapping by ultrasound, CTA or MRA. Outcomes were extracted, data meta-analysed and the quality of the evidence appraised. Results: Fourteen articles were included. Preoperative perforator mapping by CTA or MRA significantly reduced operating time (mean reduction of 54 minutes [95% CI 3, 105], p = 0.04), when directly compared to DIEP flap breast reconstruction with no perforator mapping. Further, perforator mapping by CTA was superior to ultrasound, as CTA saved more time in theatre (mean reduction of 58 minutes [95% CI 25, 91], p < 0.001) and was associated with a lower risk of partial flap failure (RR 0.15 [95% CI 0.04, 0.6], p = 0.007). All studies were at risk of methodological bias and the quality of the evidence was very low. Conclusions: The quality of research regarding perforator mapping prior to DIEP flap breast reconstruction is poor and although preoperative angiography appears to save operative time, reduce morbidity and confer cost savings, higher quality research is needed. Registration: PROSPERO ID CRD42017065012.